Diverse Gene Cassette Arrays Prevail in Commensal Escherichia coli From Intensive Farming Swine in Four Provinces of China - Zhang, Xiuping; Li, Xinxin; Wang, Weihua; Qi, Jiali; Wang, Dong; Xu, Lei; Liu, Yong; Zhang, Yanming; Guo, Kangkang (Frontiers in Microbiology, 2020)
Multiple-drug resistance bacteria containing antimicrobial resistance genes (ARGs) present are a concern for public health. Integrons are bacterial genetic elements that can capture, rearrange, and express mobile gene cassettes responsible for the spread of antimicrobial resistance genes. Few studies link genotype and phenotype of swine-related ARGs in the context of mobile gene cassette arrays among commensal Escherichia coli (E. coli) in non-clinical livestock isolates from intensive farms. In the present study, a total of 264 isolates were obtained from 330 rectal swabs to determine the prevalence and characteristics of antibiotic-resistant gene being carried by commensal E. coli in the healthy swine from four intensive farms at Anhui, Hebei, Shanxi and Shaanxi, in China. Antimicrobial resistance phenotypes of the recovered isolates were determined for 19 antimicrobials. The E. coli isolates were commonly non-susceptible to doxycycline (75.8%), tetracycline (73.5%), sulfamethoxazole-trimethoprim(71.6%), amoxicillin(68.2%), sulfasalazine (67.1%), ampicillin (58.0%), florfenicol (56.1%) and streptomycin(53.0%), but all isolates were susceptible to imipenem (100%). 184 (69.7%) isolates exhibited multiple drug resistance with 11 patterns. Moreover, 197 isolates (74.6%) were detected carrying the integron-integrase gene (intI1) of class 1 integrons. A higher incidence of antimicrobial resistance was observed in the intI1-positive E. coli isolates than in the intI1-negative E. coli isolates. Furthermore, there were 17 kinds of gene cassette arrays in the 70 integrons as detected by sequencing amplicons of variable regions, with 66 isolates (94.3%) expressing their gene cassettes encoding for multiple drug resistance phenotypes for streptomycin, neomycin, gentamicin, kanamycin, amikacin, sulfamethoxazole-trimethoprim, sulfasalazine and florfenicol. Notably, due to harboring multiple, hybrid and recombination cassettes, complex cassettes arrays attributed to multiple drug resistance patterns than simple arrays did. In conclusion, we demonstrated that the prevalence of multiple drug resistance and the incidence of class 1 integrons were 69.7% and 74.6% in commensal E. coli isolated from healthy swine, which were lower frequency than the previously reported in China.